VALIDITY OF GUIDED INQUIRY-BASED PHYSICS LEARNING MODULE - silaban, eka setiaji; Siregar, Alkhafi Maas (Journal of Learning and Technology in Physics, 2024)
The learning resources used in learning physics class XI SMAN 1 Namorambe is only a package book. In fact, teachers and students are not satisfied with the existing learning resources, therefore a new learning resource is needed and is expected to meet the needs of teachers and students. This research focuses on the development of physics learning modules on sound waves material class XI SMA. This study aims to determine the validity level of the guided inquiry-based module on the subject of sound waves that have been developed. This research is an R & D (Research and Development) development research using the 4-D model which has four main stages, namely the defining stage (define), the design stage (Design), the development stage (Development), and the dissemination stage (disseminate). The research instruments used are validation instruments consisting of validation instruments by material experts and media expert validation instruments. The results showed that the validity level of the guided inquiry-based physics learning module produced was on very valid criteria so it was feasible to use in learning.